Low molecular mass chondroitin sulfate suppresses chronic unpredictable mild stress-induced depression-like behavior in mice - Si Xiao-Ming; Tian Yu-Hua; Zhang Sha-Sha; Gao Hua; Liu Kun; Jin Jing-Yu (Acta Pharmaceutica)
The present study is aimed at testing the antidepressant--like effects and probable mechanisms of action of low molecular mass chondroitin sulfate (LMMCS) on depression induced by chronic unpredictable mild stress (CUMS) in mice. Four weeks of CUMS exposure resulted in depressive-like behavior, expressed by a significant decrease in the locomotor activity and sucrose consumption and increased immobility time in the forced swim test. Further, there was a significant reduction of 5-HT level in the hippocampus region of depressed mice. Treatment of mice for four weeks with LMMCS ameliorated significantly both the behavioral and biochemical changes induced by CUMS. These novel results suggest that LMMCS produces an antidepressant-like effect in mice subjected to CUMS, which might be related, at least in part, to the increase of 5-HT concentration in the hippocampus.